Do hiring practices penalize women and benefit men for having children? Experimental evidence from Germany - Lena Hipp (European Sociological Review, 2020)
Although observational studies from many countries have consistently shown that motherhood negatively affects women's wages, experimental findings on its effect on the likelihood of being hired are less conclusive. Motherhood penalties in hiring have been reported in the US, the prototypical liberal market economy, but not in Sweden, the prototypical social-democratic welfare state. Based on a field experiment in Germany, this study examines the effects of parenthood on hiring processes in the prototypical conservative welfare state. My findings indicate that job recruitment processes indeed penalize women but not men for having children. In addition to providing theoretical explanations for why motherhood penalties in hiring are particularly likely to occur in the German context, this study also highlights several methodological and practical issues that should be considered when conducting correspondence studies to examine labor market discrimination.
Keywords: 330; gender; parenthood; discrimination; field experiment